Scientific Opinion of the EFSA Panel on Plant Protection Products and their Residues (PPR) on the science behind the development of a risk assessment of plant protection products on bees (Apis mellifera, Bombus spp., and solitary bees) - EFSA Panel on Plant Protection Products and their Residues (PPR); Christiane Vleminckx (EFSA Journal, 2012)
The PPR Panel was asked to deliver a scientific opinion on the science behind the development of arisk assessment of plant protection products on bees (
Keywords: approach; approaches; assessment; Categories; data; Development; Ecosystem; effect; effects; exposure; Guidance Document,PPR opinion,honey bees,bumble bees,solitary bees,pesticide,risk assessment; Guidelines; Improvement; IS; mortality; need; needs; ON; pesticide; Pesticides; plant; plant protection product; PRODUCTS; repeated; Research; Residue; risk; Risk Assessment; Science; Service; Services; specific; Test